"Topological space and continuous reflections" - Ismoilov Davronbek Ilhomjon o‘g‘li (Genius Publishing Group, 2022)
This article describes the main objects of topology and topological space, the essence of topological reflections, one of the basic concepts of topological space.
Keywords: Topological; Analysis Situs; Geometry And Mathematics; Figure